Protein fibrillation lag times during kinetic inhibition - Pagano, Rodrigo Sebastián (2014)
Protein aggregation is linked to more than 30 human pathologies, including Alzheimer's and Parkinson's diseases. Since small oligomers that form at the beginning of the fibrillation process probably are the most toxic elements, therapeutic strategies involving fibril fragmentation could be detrimental. An alternative approach, named kinetic inhibition, aims to prevent fibril formation by using small ligands that stabilize the parent protein. The factors that govern fibrillation lag times during kinetic inhibition are largely unknown, notwithstanding their importance for designing effective long-term therapies. Inhibitor-bound species are not likely to be incorporated into the core of mature fibrils, although their presence could alter the kinetics of the fibrillation process. For instance, inhibitor-bound species may act as capping elements that impair the nucleation process and/or fibril growth. Here, we address this issue by studying the effect of two natural inhibitors on the fibrillation behavior of lysozyme at neutral pH. We analyzed a set of 79 fibrillation curves obtained in lysozyme alone and a set of 37 obtained in the presence of inhibitors. We calculated the concentrations of the relevant species at the beginning of the curves using the inhibitor-binding constants measured under the same experimental conditions. We found that inhibitor-bound protein species do not affect fibrillation onset times, which are mainly determined by the concentration of unbound protein species present in equilibrium. In this system, knowledge of the fibrillation kinetics and inhibitor affinities suffices to predict the effect of kinetic inhibitors on fibrillation lag times. In addition, we developed a new methodology to better estimate fibrillation lag times from experimental curves.